2005
DOI: 10.1007/s00246-004-0742-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coenzyme Q10 on Idiopathic Chronic Dilated Cardiomyopathy in Children

Abstract: The objective of this study was to assess the effect of coenzyme Q10 (CoQ10) as supplementation to conventional antifailure drugs on quality of life and cardiac function in children with chronic heart failure due to dilated cardiomyopathy (DCM). The study was an open-label prospective study performed in two of the largest pediatric centers in Thailand from August 2000 to June 2003. A total of 15 patients with idiopathic chronic DCM were included, with the median age of 4.4 years (range, 0.6-16.3). Presenting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
14
0
2
Order By: Relevance
“…In children with dilated cardiomyopathy, CoQ 10 may improve the cardiothoracic ratio and shorten ventricular depolarization and NYHA class [122]. In a prospective RCT (duration 6 months) in children with dilated cardiomyopathy, the administration of CoQ 10 resulted in a lower mean score for the index of cardiac failure (p < 0.024 compared to placebo) and in improvement of diastolic function (p < 0.011 compared to placebo) [123].…”
Section: Coq 10 and Nonischemic Cardiomyopathiesmentioning
confidence: 98%
“…In children with dilated cardiomyopathy, CoQ 10 may improve the cardiothoracic ratio and shorten ventricular depolarization and NYHA class [122]. In a prospective RCT (duration 6 months) in children with dilated cardiomyopathy, the administration of CoQ 10 resulted in a lower mean score for the index of cardiac failure (p < 0.024 compared to placebo) and in improvement of diastolic function (p < 0.011 compared to placebo) [123].…”
Section: Coq 10 and Nonischemic Cardiomyopathiesmentioning
confidence: 98%
“…A recent review has focused on the multiple implications of CoQ10 deficiency and of CoQ10 administration encompassing an extensive number of disorders [ 100 ]. Out of 101 reports on clinical trials testing CoQ10, 39 studies were focused on support to patients with heart and vessel disorders or undergoing heart surgery [ 11 , 12 , 81 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ], including 32 controlled studies, as shown in Table 2 . The pioneering studies by the groups of Tanaka [ 11 ] and of Langsjoen [ 12 ] since 1982 provided the avenue for a number of clinical trials assessing the successful outcomes of CoQ10 administration to patients with coronary artery disease, cardiomyopathy, heart failure, or heart surgery, with an overall SR = 0.89.…”
Section: Coenzyme Q10mentioning
confidence: 99%
“…They measured symptoms, ejection fraction, left ventricular size, and quality of life measurements before and after treatment with CoQ 10 . Although they show dramatic improvements, severe study design flaws have limited their applicability [28][29][30][31][32][33][34][35].…”
Section: Intervention Studies With Coenzyme Q 10 In Heart Failurementioning
confidence: 99%